Analisis Risiko Kegagalan Genset Cummins Berbasis FMEA dalam Perspektif Reliability-Centered Maintenance di CV X - Hakim, Ilham Luqmanul; Sundari, Susanti; Suwarni, Putri Endah; Nudin, Burhan (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
CV. X frequently experiences recurring failures in Cummins genset components, such as rubber coupling, fuel filter, oil filter, battery, and radiator. This condition causes considerable downtime and increased maintenance costs, as the maintenance approach remains reactive. This research aims to design a more effective maintenance strategy using the Reliability Centered Maintenance (RCM) method. Data were collected through observation, interviews, and failure history records, then analyzed using Failure Mode and Effect Analysis (FMEA) to identify critical components, as well as Logic Tree Analysis (LTA) to determine the appropriate maintenance strategy. The results revealed five critical components, with the highest risk value found in the rubber coupling(RPN 300). The recommended strategy is Condition Directed for the rubber coupling, battery, and radiator, and Time Directed for the fuel filter and oil filter. Implementing this strategy is expected to reduce downtime and improve machine reliability. Keywords: Cummins Genset, Downtime, Logic Tree Analysis (LTA), Maintenance, RCM